2014
DOI: 10.1530/joe-13-0484
|View full text |Cite
|
Sign up to set email alerts
|

Combining sitagliptin/metformin with a functional fiber delays diabetes progression in Zucker rats

Abstract: Our primary objective was to determine whether administering the viscous and fermentable polysaccharide PolyGlycopleX (PGX) with metformin (MET) or sitagliptin/metformin (S/MET) reduces hyperglycemia in Zucker diabetic fatty (ZDF) rats more so than monotherapy of each. Glucose tolerance, adiposity, satiety hormones and mechanisms related to dipeptidyl peptidase 4 activity, gut microbiota and, hepatic and pancreatic histology were examined. Male ZDF rats (9-10 weeks of age) were randomized to: i) cellulose/vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 51 publications
2
17
1
Order By: Relevance
“…Reimer et al reported a delay in diabetes progression in obese male ZDF rats treated with a viscous and fermentable fiber, PolyGlycopleX (PGX), combined with two drugs, sitagliptin and metformin [38]. Our current study and the Reimer et al study indicated that improved insulin sensitivity is possible in obese ZDF rats and an isolated prebiotic is effective in improving insulin sensitivity.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Reimer et al reported a delay in diabetes progression in obese male ZDF rats treated with a viscous and fermentable fiber, PolyGlycopleX (PGX), combined with two drugs, sitagliptin and metformin [38]. Our current study and the Reimer et al study indicated that improved insulin sensitivity is possible in obese ZDF rats and an isolated prebiotic is effective in improving insulin sensitivity.…”
Section: Discussionsupporting
confidence: 63%
“…Reimer et al. reported a delay in diabetes progression in obese male ZDF rats treated with a viscous and fermentable fiber, PolyGlycopleX (PGX), combined with two drugs, sitagliptin and metformin . Our current study and the Reimer et al.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, Matveyenko et al [26] reported a synergistic effect of the combination of both sitagliptin and metformin in controlling body weight in a human islet amyloid polypeptide (HIP) transgenic rat model of type 2 diabetes, rather either agent alone. In addition, Reimer et al [32] reported similar findings in the Zucker diabetic fatty rat model of type 2 DM. These results indicated an effective combination of both sitagliptin and metformin in maintaining body weight in different animal models of type 2 DM.…”
Section: Discussionmentioning
confidence: 70%
“…Reimer et al demonstrated that co-administration of sitagliptin and a viscous fermentable fibre, which is broken down into SCFA, more effectively reduced fasting glycaemia in obese Zucker rats than either treatment alone [53]. Similar results were obtained in the same model when this fibre was combined with metformin or with metformin and sitagliptin [54].…”
Section: Dysbiosis Related To Type 2 Diabetes and Hyperglycaemiamentioning
confidence: 86%